LncRNA IGHCγ1 Acts as a ceRNA to Regulate Macrophage Inflammation via the miR-6891-3p/TLR4 Axis in Osteoarthritis. (17th January 2020) - Zhang, Pengjun; Sun, Jianmei; Liang, Caihong; Gu, Bingjie; Xu, Yang; Lu, Hongying; Cao, Bo; Xu, Hao
Abstract : Accumulating data have implicated that long noncoding RNA (lncRNA) plays an important role in osteoarthritis (OA), which may function as a competitive endogenous RNA (ceRNA) of microRNAs (miRNAs). lncRNA IGHC γ 1 has been demonstrated to regulate inflammation and autoimmunity. Nonetheless, the altering effect of IGHC γ 1 in OA remains unclear. This study is aimed at investigating the mechanism and function of lncRNA IGHC γ 1 in OA. CCK-8, EdU, and transwell assays were used to estimate macrophage proliferation and migration. Fluorescence in situ hybridization (FISH) was performed to estimate the local expression of lncRNA IGHC γ 1 in macrophages. Luciferase reporter assay was adopted to validate the ceRNA role of IGHC γ 1 as miRNA sponge. lncRNA IGHC γ 1 was primarily localized in macrophage cytoplasm and upregulated in OA. miR-6891-3p inhibited macrophage proliferation, migration, and inflammatory response by targeting TLR4, while lncRNA IGHC γ 1 promoted TLR4 expression by functioning as a ceRNA for miR-6891-3p through the NF- κ B signal in macrophages. This study strongly supports that lncRNA IGHC γ 1 regulates inflammatory response via regulating the miR-6891-3p/TLR4/NF- κ B axis in macrophages.